Estradiol Increases ip3 by a Nongenomic Mechanism in the Smooth Muscle Cells from the Rat Oviduct - Orihuela-Diaz, P; Reuquen-Lopez, P; Diaz-Saldivar, P; Orostica, M (BioScientifica Ltd., 2015)
Estradiol (E2) accelerates egg transport by a nongenomic action, requiring activation of estrogen receptor (ER) and successive cAMP and IP3 production in the rat oviduct. Furthermore, E2increases IP3production in primary cultures of oviductal smooth muscle cells. As smooth muscle cells are the mechanical effectors for the accelerated oocyte transport induced by E2in the oviduct, herein we determined the mechanism by which E2increases IP3in these cells. Inhibition of protein synthesis by Actinomycin D did not affect the E2-induced IP3increase, although this was blocked by the ER antagonist ICI182780 and the inhibitor of phospholipase C (PLC). ET-18-OCH3. Immunoelectron microscopy for ESR1 or ESR2 showed that these receptors were associated with the plasma membrane, indicating compatible localization with E2nongenomic actions in the smooth muscle cells. Furthermore, ESR1 but not ESR2 agonist mimicked the effect of E2on the IP3level. Finally, E2stimulated the activity of a protein associated with the contractile tone, calcium/ calmodulin-dependent protein kinase II (CaMKII), in the smooth muscle cells. We conclude that E2increases IP3by a nongenomic action operated by ESR1 and that involves the activation of PLC in the smooth muscle cells of the rat oviduct. This E2effect is associated with CaMKII activation in the smooth muscle cells, suggesting that IP3and CaMKII are involved in the contractile activity necessary to accelerate oviductal egg transport. © 2015 Society for Reproduction and Fertility.